2023
DOI: 10.1101/2023.06.26.546598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hundreds of myosin 10s are pushed to the tips of filopodia and could cause traffic jams on actin

Abstract: Myosin 10 (Myo10) is a vertebrate-specific motor protein well known for its role in filopodia formation. Although Myo10-driven filopodial dynamics have been characterized, there is no information about the numbers of Myo10 in filopodia. To better understand molecular stoichiometries and packing restraints in filopodia, we measured Myo10 abundance in these structures. Here we combined SDS-PAGE analysis with epifluorescence microscopy to quantitate HaloTag-labeled Myo10 in U2OS cells. About 6% of total intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
1
1
Order By: Relevance
“…This point further implies that the number of myosins promoting elongation may be set at the initiation of filopodial growth. In contrast to our findings, a recent study in U2OS cells demonstrated that over-expression of Myo10FL leads to filopodial tips that contain hundreds of motors (median of ~360 molecules), with a large range around this value (2-65,000 molecules) (33). Although we employed a direct single molecule visualization strategy, that study used a population level biochemical approach combined with epifluorescence microscopy to approximate the number of motors in individual cells, and in turn, single filopodia.…”
Section: Discussioncontrasting
confidence: 99%
“…This point further implies that the number of myosins promoting elongation may be set at the initiation of filopodial growth. In contrast to our findings, a recent study in U2OS cells demonstrated that over-expression of Myo10FL leads to filopodial tips that contain hundreds of motors (median of ~360 molecules), with a large range around this value (2-65,000 molecules) (33). Although we employed a direct single molecule visualization strategy, that study used a population level biochemical approach combined with epifluorescence microscopy to approximate the number of motors in individual cells, and in turn, single filopodia.…”
Section: Discussioncontrasting
confidence: 99%
“…Myosin motors accumulated at the protrusion tip could contribute to combatting this force, as well as create space for polymerization to occur. Recent data published by Shangguan and Rock ( 62 ) estimates ∼360 MYO10 molecules occupy a single filopodium, distributed mostly at the protrusion tip ( 62 ). Given that a single molecule of MYO10 can generate a maximum force of ∼1pN per single step ( 31 ) with a duty ratio of roughly 60% ( 48 ), an ensemble of ∼100 active MYO10 molecules at the protrusion tip could contribute around 60pN of tip-ward force along the membrane per step.…”
Section: Discussionmentioning
confidence: 99%